Dopant migration-induced interface dipole effect in n-doped GaAs/AlGaAs terahertz detectors - Jit S.; Weerasekara A.B.; Jayasinghe R.C.; Matsik S.G.; Perera A.G.U.; Buchanan M.; Sproule G.I.; Liu H.C.; Stintz A.; Krishna S.; Khanna S.P.; Lachab M.; Linfield E.H. (My University, 2025)
A heterojunction interfacial workfunction internal photoemission (HEIWIP) terahertz detector with ∼1 × 1018 cm-3 n-type doped GaAs emitters in a multilayer GaAs/Al0.13Ga0.87As heterostructure is presented. The detection mechanism is based on free carrier absorption with a broad response extending to ∼5.26 THz (57 ∼m), corresponding to an effective workfunction of ∼21.8 meV, which is much smaller than the offset expected for an Al fraction of x = 0.13 at a 1 × 1018 cm-3 doping. This is attributed to a reduction of the conduction band offset by interface dipole formation between the accumulated negative charges at the interface states and migrated positively charged donors in the barrier. The device has a peak responsivity of 0.32 A/W at ∼26 μm at 5 K. It is demonstrated that the dopant migration-induced interface dipole effect can be used to extend the zero response threshold frequency f0 of n-type HEIWIP detectors. © 2008 IEEE.